Unnatural deaths among children in the Transkei region of South Africa - Meel, B.L. (Medicine, science, and the law, 2008)
Nearly 99% of the 10.9 million children worldwide under the age of five years who died in 2000 were from developing countries. This amounts to at least 29,000 deaths per day (UNICEF, 2005). This study aims to trace the pattern of unnatural deaths in the Transkei region of South Africa. It is a records review of the medico-legal autopsies carried out between 1996 and 2004 at Umtata General Hospital (UGH). All subjects aged 18 years or below were considered as children. Between 1996-2004, 7,303 unnatural deaths were recorded. Of these, 1,449 (19.8%) were children. Trauma accounted for 1,028 (70.9%) child deaths and 421 (29.1%) were deaths related to other causes such as hanging, burns, lightning strike, drowning, gas suffocation, falls from a height and poisoning. Motor vehicle accidents accounted for 469 (45.6%) deaths and homicides for 553 (54.4%) deaths. The homicides were firearms injuries, 196 (19%), stab wounds, 185 (18%), and blunt trauma, 178 (17.3%). Non-traumatic deaths were hanging, 81 (19.2%), drowning, 166 (39.4%), lightning strike, 38 (9%), burns, 51 (12.1%), gas suffocation, 24 (5.7%), poisoning, 33 (8.4%) and falls from a height 28 (6.7%). There is a high risk of unnatural death among children in the area of Mthatha. It threatens the survival of young children in this region of South Africa. Poverty is an underlying cause for these preventable deaths.